1996
DOI: 10.1063/1.51582
|View full text |Cite
|
Sign up to set email alerts
|

Rapid follow-up ROSAT observation of GRB 940301

Abstract: Abstract. The strong γ-ray burst of March 1, 1994 was imaged by COMPTEL and found to have an identical location within the errors as a burst which occurred on July 4, 1993. This location coincidence had prompted speculations on a possible single source origin for both bursts.We have performed a ROSAT PSPC mosaic observation within four weeks of GRB 940301. The results of these observations and the comparison of the intensities of the detected sources with those detected during the ROSAT all-sky-survey in Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…ROSAT pointed observations were initiated within 4 weeks of two GRBs, namely GRB 920501 (Li et al, 1996) and 940301, which due to their close locations had been dubbed "COMPTEL repeater" GRB 930704/ 940301 (Greiner et al, 1996). None revealed a fading X-ray counterpart.…”
Section: Rapid Follow-up Observations Of Grbsmentioning
confidence: 99%
“…ROSAT pointed observations were initiated within 4 weeks of two GRBs, namely GRB 920501 (Li et al, 1996) and 940301, which due to their close locations had been dubbed "COMPTEL repeater" GRB 930704/ 940301 (Greiner et al, 1996). None revealed a fading X-ray counterpart.…”
Section: Rapid Follow-up Observations Of Grbsmentioning
confidence: 99%
“…Other areas of GRB research with ROSAT can be found elsewhere, such as the investigation of small IPN error boxes using the ROSAT all-sky survey data in Boër et al (1994), a summary of all ROSAT pointings on GRB error boxes and a correlation of GRB locations with serendipituous ROSAT pointings in Greiner (1997). (12) data not yet available during writing.…”
Section: Introductionmentioning
confidence: 99%